ANALISIS PENERAPAN PSAK NO. 36 TENTANG AKUNTANSI KONTRAK ASURANSI JIWA (Studi Kasus PT. Asuransi Jiwasraya (Persero) Cabang Jambi) - Permatasari, Ariadna; Tjandrakirana, Rina; Meirawati, Eka (Universitas Muhammadiyah Palembang, 2018)
The purpose of this study is to analyze the application of SFAS No. 36 about accounting forlife insurance contract at PT. Asuransi Jiwasraya (Persero) Branch of Jambi City. Type ofresearch in this study is qualitative research by using case study research. Data collectionmethods used in this study are interviews and documentation. Sources of data used in thisstudy are primary data and secondary data. The method of data analysis in this study isdescriptive analysis, which defined as a method that is only used to describe, identify, oranalyze the results of research but not used to make a conclusion broader.The result showed that PT. Asuransi Jiwasraya (Persero) Branch of Jambi City has not fullyimplemented SFAS No. 36, since the recognition of other income is not derived from thecommissions on reinsurance and commissions profit butratherfrom the policy payable as wellas the recognition and measurement of future benefits liability policy and estimated claimsliability are not done by the branch office but by the head office. The company does not makeany notes to the financial statements, so there is no accounting policy disclosure. Thecompany should follow the development of the Financial Accounting Standards by applyingSFAS No. 36.